Unravelling Facebook: a pedagogical tool during the Syrian crisis. (2nd September 2017) - Ramadan, Reem
ABSTRACT: This paper aims to analyse the role of Facebook in academia during the Syrian crisis. Data were collected by means of an online survey from 726 students at Damascus University (Males = 446, Females = 280). Results indicated that Facebook facilitated communication and resource sharing in times of war and crisis where safe commuting posed a challenge for students. It served as an alternate trustworthy medium within the failure of the official web sites at Damascus University. The study suggests that Facebook is an effective pedagogical tool for countries going through crisis and war situations, and a promising educational tool that warrants further attention in underdeveloped and Arab countries in general.